(untitled) (Applied Biological Research, 2022)
Protozoans exhibit highly diverse ecological inter-relationship and most complicated host-relationship. The catfish Clarias sp. is important component in human diet in many countries especially those in tropical and subtropical areas where malnutrition is a major problem. Clarias sp. (size 20-22 cm, weight 80-90 g) were collected from a local fish market of Kolkata (India) during pre-monsoon, monsoon and post-monsoon seasons of 2017-2019. The blood, gill and skin of catfish were examined in laboratory for protozoan parasites and routine histopathological study of selected tissues was performed. Photo-documentation was done using microscope-fitted with digital camera. The study revealed that the intensity of infection was more in ciliate parasites, and the fish had marked lesions in gills and skin. The highest parasitic infection was observed in post-monsoon season i.e. from November to Februaryfollowed by pre-monsoon period; while the lowest infection was noted in monsoon season i.e. from July to October. The study revealed that the environmental factors are responsible for spreading infection.